Peer assisted learning in higher education: Roles, perceptions and efficacy - Chan, Nee Nee *; Phan, C. W.; Aniyah, Salihan N. H.; Dipolog-Ubanan, G. F. (Universiti Putra Malaysia, 2016)
Universities are increasingly examining alternative means of teaching and learning, and supplemental instruction in the form of peer tutoring is progressively used to support learning in selected courses. This small scale ethnographic study investigates the roles and relationships between the peer tutors and tutees to uncover their perceptions of peer tutoring and their perceived effects. Semi-structured focus group discussions of ten tutors and ten tutees and two participant group observations were employed. The findings suggest that perceptions of the success of this programme were attributed to low power distance of the tutors and tutees, the development of friendships and the metacognitive learning strategies that were explicitly taught. Implications arising from this study suggest a greater focus on roles and expectations in the design of peer tutoring programmes.